Risk Factors for Bovine Cysticercosis in North-West Italy: A Multi-Year Case-Control Study - Selene Rubiola (MDPI AG, 2021)
Taenia saginata is the causative agent of bovine cysticercosis, a zoonotic parasitic disease with a worldwide distribution. Bovine cysticercosis is considered to be an important food safety issue responsible for human taeniasis and a major economic concern since infected carcasses undergo condemnation, freezing and downgrading. The aim of the current investigation was to assess the presence of farm-level risk factors for bovine cysticercosis in an endemic area in North-West Italy. A questionnaire was designed to collect information relating to several farm structural features, as well as management practices, environmental characteristics and attitudes of farmers. The questionnaire was administered in two separate time intervals by direct interview to previously selected case and control farms. Overall, 32 case farms and 131 control farms were included between 2005 and 2011 and 50 case farms and 192 control farms were included between 2014 and 2020. The present survey showed a significant association between the detection of bovine cysticercosis cases at slaughter and farm proximity to picnic spots, closeness of wastewater treatment plant effluents, loose-housing systems and presence of employees along with the family members, highlighting the need for targeted awareness raising policies.